Polymeric fluorescent heparin as one-step FRET substrate of human heparanase. (1st February 2019) - Sistla, Jyothi C.; Morla, Shravan; Alabbas, Al-Humaidi B.; Kalathur, Ravi C.; Sharon, Chetna; Patel, Bhaumik B.; Desai, Umesh R.
Highlights: Development of polymeric heparin as a FRET substrate of heparanase. The FRET substrate enables rapid, one-step screening of heparanase inhibitors. The FRET substrate enables monitoring of heparanase activity in biological media. Abstract: Heparanase, an endo-β- D -glucuronidase, cleaves cell surface and extracellular matrix heparan sulfate (HS) chains and plays important roles in cellular growth and metastasis. Heparanase assays reported to-date are labor intensive, complex and/or expensive. A simpler assay is critically needed to understand the myriad roles of heparanase. We reasoned that fluorescent heparin could serve as an effective probe of heparanase levels. Following synthesis and screening, a heparin preparation labeled with DABCYL and EDANS was identified, which exhibited a characteristic increase in signal following cleavage by human heparanase. This work describes the synthesis of this heparin substrate, its kinetic and spectrofluorometric properties, optimization of the heparanase assay, use of the assay in inhibitor screening, and elucidation of the state of heparanase in different cell lines. Our FRET-based assay is much simpler and more robust than all assays reported in the literature as well as a commercially available kit.